A comparative economic study on improved and non-improved native chicken practices in some selected areas of Bangladesh (Bangladesh Journal of Livestock Research, 2021)
Native chickens are important for the rural poor women and marginalized section for subsidiary income and safe nutrition. Considering that views, the study were conducted taking objectives is assessing the profitability of native chicken and to find the livelihood status of native chicken farmers. The study areas were selected from six districts, namely, Joypurhat Sadar under Joypurhat, Dinajpur Sadar under Dinajpur, Dumoria under Khulna, Kotalipara under Gopalgonj, Nokla under Sherpur and Sonagazi under Feni district on the basis of improved native chickens project implementation areas. The selected areas were consisted of 30 treatment groups and 30 control groups from each upazila. The total sample size was 360 (P/H). In the case of profitability, the treatment group earned BDT 3,450 per 10 birds per annum followed by control group earned BDT 2,476. The BCR was found 2.04 and 1.45, respectively for treatment and control group. It was evident that treatment group produced 60 native chickens annually and on the other hand, control group produced 30 native chickens. For control group, labour cost occupied 32 percent and the feed cost captured 23 percent. On the other hand, for treatment group, feed cost occupied 34 percent and the labour cost was 38 percent. Fifty percent farmers opined that they reared native chicken for additional family income followed by 37 percent home consumption, 9 percent ceremonies and 4 percent creating employment opportunity. Rearing of native chicken entirely depends on women’s decision but the usage of money is controlled by women and men. It was found that women dominated most activities in rearing native chicken. Based on the result of the study, 100 percent women was the decision maker for rearing native chicken in both groups. Decision on selling of native chicken made by women was 92.15 percent in treatment group and 73.28 percent in control group. Money received from native chicken was also controlled 78.26 percent in treatment group and 51.57 percent in control group by women. Lack of access to livestock extension service, bad eggs quality, access to credit also was the challenges for native chicken farmers covering 7 percent, 4 percent and 4 percent, respectively. From this study, it was clear that rearing native chicken farming brought positive changes in economic, social and specially women empowerment indicators.Bang. J. Livs. Res. Vol. 27 (1&2), 2020: P. 24-38